Empowerment of the Fishermen's Wives in Nagari Sungai Pinang through Mangrove Batik Craft in Realizing the Green Economy in Marine Tourism Areas: Pemberdayaan Istri Nelayan Nagari Sungai Pinang Melalui Kerajinan Batik Mangrove dalam Mewujudkan Green Ekonomi di Kawasan Wisata Bahari - Murhenna Uzra; Mistia Sari; Rama Wahyudin; Dertha Mukhtar; Gingga Prananda; Reffi Aryzegovina (The Future of Education Journal, 2025)
The mangrove forest growing along the coast of Sungai Pinang functions as a natural barrier against abrasion, a habitat for various marine biota, and a provider of essential nutrients within the coastal ecosystem chain. However, current conditions indicate that the existence of mangroves in this area continues to be threatened by human activities and the suboptimal management and utilization of the area in a sustainable manner. The main problem faced by the partner community is the lack of optimal community empowerment, particularly among fishermen’s wives, in managing and utilizing mangrove plants as an alternative economic resource. Previous conservation and educational activities were temporary and unsustainable due to limited assistance from official institutions and weak access to training, capital, and production materials. This has hindered the development of creative economic activities based on mangrove potential, such as handicrafts, batik production, and processed coastal food products. The implementation method is designed systematically and participatively so that the proposed solutions can be effectively adopted by the target partners through training and outreach. The primary goal of this program is to empower fishermen’s wives in Nagari Sungai Pinang through mangrove-based batik crafts as an economic resource, in order to realize the concept of a Green Economy in coastal areas that emphasizes environmental conservation, improved welfare, and sustainable development. The results of this program include the establishment of a creative group of fishermen’s wives producing mangrove batik, which serves as a medium for promoting coastal environmental conservation and positioning mangrove batik as a maritime tourism icon in Nagari Sungai Pinang.